Superconducting Magnetic Energy Exchange Modelling and Simulations under Power Swell/Sag Conditions. (May 2017) - Chen, Xiao Yuan; Feng, Juan; Tang, Mian Gang; Xu, Qiang; Li, Guo Hui
Abstract: This paper presents a simplified superconducting magnetic energy exchange (SMEE) model for the potential use in the parameter design and performance evaluation of superconducting magnetic energy storage (SMES) devices prior to their practical developments and applications in modern power system. In this model, the targeted power system applications are transformed into equivalent energy exchange demands for the SMES coils in a simplified DC power network without conventional DC-AC power devices. Both the steady-power and dynamic-power energy exchange simulations are carried out to clarify the feasibility of the proposed SMEE model for the design, optimization and evaluation of a practical SMES device.